The role and mechanism of TNFRSF21 in promoting necroptosis of vascular endothelial cells and inducing vascular leakage in sepsis - Juntao Wang; Bindan Zhang; Yujia Wu; Weichao Li; Yuxi Zhang; Daiqin Bao; Haoyu Pei; Caifeng Shi; Han She; Xiaoyan Wang; Qingxiang Mao; Cong Yu (Journal of Molecular Medicine, 2026)

Dynamic bi-domain discriminator adversarial network for EEG emotion recognition - Leyang Yu; Qingshan She; Zizhuo Wu; Zhaowen Xiao; Ming Meng; Kun Luo (Cognitive Neurodynamics, 2026)

Discovery of swertimusins A‒D: Four pairs of rearranged nor-secoiridoid derivatives with a hexahydrofuro[2,3-b]furan ring from Swertia mussotii - Xue Cheng; Qi-Feng Zhang; Rui-Kang Tan; Wen-Di Wang; Yu-Rui Dou; Jia-Yi Wei; Ke-Xun She; Xiao-Feng He (Phytochemistry, 2026)

Variations of F-Cl-Br-I in the Pinghe alkaline complex (South China): Constraints on halogen budgets of the metasomatized lithospheric mantle - Dan-Zhen Ma; Lian-Xun Wang; Sebastian Tappe; Yu-Xiang Zhu; Zhen-Bing She; Chao Zhang (Chemical Geology, 2026)

Aging and photodegradation of polycyclic aromatic compounds (PACs) emitted from biomass burning under sunlight and ultraviolet radiation - Ya-Jing Li; Zhen-Shan Huang; Yu-Ping Chen; Zhi-Hui Su; Yi-Huan Chen; Yuan Zeng; Yu-Qi Huang; Yu-Feng Guan; She-Jun Chen (Atmospheric Environment, 2026)

Bioavailable fractions drive variations in riverine dissolved organic nitrogen along land-use gradients - Yan Ding; Yaning Yang; Ting Pan; Yuecheng She; Chang Liu; Juan Zhao; Xiaowei Liu; Qingbo Yu; Fengyu Zan (ENGINEERING Environment, 2026)

The oxidative potential of PM2.5 outperforms its mass concentration in association with childhood sleep disorders: Evidence from a large-scale study in China - Yun-Hui Shao; Dan Cai; Qian Yao; Xi-Hua Lin; Jin-Shan Ge; Lu-Yin Wu; Yun-Jiang Yu; Guang-Hui Dong; She-Xia Ma (Environmental Pollution, 2026)

Synergistic engineering of oxygen vacancies and AuCu interface on ZnO for enhanced photocatalytic biomass valorization - Hao-Yu Chen; Wu-Dan Yang; Jie-Yang Dong; Ling-Bao Wu; Dan-Dan She; Ze-Kuan Zhang; Tian-Jun Gong; Qi Zhang; Yao Fu (Chemical Engineering Journal, 2026)

Metabolic rewiring and transcriptional interference underlie the biocontrol efficacy of Burkholderia arboris BB417 against Ralstonia solanacearum species complex - Shanwen Ding; Juan Zhang; Yang Wang; Guobing Lan; Lin Yu; Yafei Tang; Zhenggang Li; Bin Guo; Zifu He; Xiaoman She (Pesticide Biochemistry and Physiology, 2026)

Particle Type- and Morphology-Associated Neurotoxicity of Microplastics and Nanoplastics via Divergent PPARγ Modulation in Zebrafish - Chenchen Han; Lixia Peng; Xinlei Guo; Yaqi Yu; Mingming Niu; Willie J.G.M. Peijnenburg; Zhiqiang Li; Xilin She; Chuanhong Wu; Lianzhen Li (Journal of Hazardous Materials, 2026)

Improved half-hourly carbon flux simulation of China's forest ecosystems: An ensemble machine learning approach with limited meteorological data - Chongyang Dong; Yu Wang; Yongshuai She; Li Zhou (Journal of Environmental Management, 2026)

Assessing additive interactions of heat wave, fine particulate matter, and ozone on cardiovascular mortality in a typical cold region of China: A time-stratified case-crossover study - Jinghao Wan; Mingzhao She; Hanhan Wang; Lixin Zheng; Xinyue Yu; Yuqian Song; Zhongran Wang; Min Li; Xu Han; Haibo Zhou; Zhifeng Xing; Xiao Bai; et al. (International Journal of Hygiene and Environmental Health, 2026)

Jet plasma-induced synthesis of chitosan-gallic acid copolymers: Structural and dual regulation of oxidative stress and inflammation - Peng Chen; Zichun Xia; Sisi Kong; Wujin Yu; Jian Wang; Ahsan Hafiz Muhammad; Tingting Bu; Yan Wang; Ming Cai; Yuanbin She (Chemical Engineering Journal, 2026)

Joint effects of social determinants of health on NAFLD mortality: the mediating role of phenotypic age acceleration - Xingyong Huang; Xiaoyue Zhang; Xin Yu; Tingting Wang; Yumo She; Mengyao Wang; Yuanyuan Yang; Yicheng Liu; Lianhai Feng; Xuanyu Hao; Kai Zhang (GeroScience, 2026)

Recent advances and opportunities for multi-robot systems in oceanography - Jessica C. Garwood; Xi Yu; Geoffrey A. Hollinger; Philip B. Lundrigan; Atsuhiro Muto; Nicholas R. Rypkema; Yu She (Frontiers in Marine Science, 2026)
Autonomous multi-robot missions are revolutionizing oceanographic data collection by increasing spatial coverage, mission durations, and allowing safe access to remote and dangerous environments at a fraction of the cost of ship-based missions. While terrestrial and aerial field robotics offer several approaches for multi-robot coordination, ocean applications present unique challenges — including navigation in a time-evolving, unknown, 3D fluid environment with significant drag, limited communications, and long-duration missions without opportunities to recharge — which require tailored solutions. To promote novel solutions arising from collaborations between field robotics and oceanography, we detail recent advances in terrestrial and aerial multi-robot coordination which we contextualize in relation to oceanographic needs, distinguishing applications at the ocean surface, at depth, and between the two domains. We conclude by highlighting future research opportunities, focusing on vehicle technology, underwater networking, and de-risking. We also emphasize that oceanographic and space missions share several similarities, making the ocean an excellent test bed for future developments.

Optimized Midbrain Organoid Transplantation Restores Dopaminergic Nigrostriatal Pathway and Motor Function in Parkinson’s Disease Mouse Model - Lin-Bo Chen; Xin-Yu She; Xi Jiang; Peng-Jian Wu; Chang-Qing Zheng; Jun Yao (Neuroscience Bulletin, 2026)

Redesigning explosive sensitization pathways via enzyme-catalyzed nitrite replacement for enhanced process safety and environmental performance - Kai-yan Lu; Quan Wang; Ying-jian Cao; Jun-Zhe Wang; Jian-she Xu; Ding-yu Feng; Jia-Bao Zhang; Zheng-jie Wang (Process Safety and Environmental Protection, 2026)

Systemic crosstalk between liver and brain is associated with microplastic-induced neurobehavioral toxicity in zebrafish - Zhimin Xu; Zheng Lin; Yifan Wang; Lei Wang; Runtong Huang; Rui Du; Xinya Kang; Xueqing Chen; Shaohua She; Zhihao Xu; Shuai Xiao; Renqiang Yu (Environmental Pollution, 2026)

Identifying hotspots and impact factors of multi-type compound events over major global river basins - Lei Zou; Jiarui Yu; Gangsheng Wang; Feiyu Wang; Dunxian She; Jun Xia (Journal of Hydrology, 2026)

Development of a pomelo pectin–based microencapsulation system for Akkermansia muciniphila - Chang-Han Wang; Wen-Yu Liu; She-Ching Wu (Food Chemistry, 2026)

Natural polysaccharides for alleviating heavy metal toxicity — Recent advances and future prospects - He Liu; Yanru Li; Qiming She; Shenglong Yang; Jiameng Sun; Xinyi Zhi; Kaixuan Mao; Shixin Song; Lei Yu; Boyu Xiong (Carbohydrate Polymers, 2026)

Synergistic modulation of porosity and acidity in core–shell zeolite nanostructures for high-quality liquid fuels production - Fuhua Zhang; Yuhao Nie; Yingjie Xu; Pengpeng Wen; Yufei Liu; Wenbo Gong; Lulin Sun; Jialuo Yin; Huihui Wang; Yue Liu; Hailong Yu; Yuanbin She; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal variations of chlorinated polycyclic aromatic hydrocarbons in Yellow Sea sediments: An eight-year field monitoring study - Xin Yang; Yunyong She; Qian Zhao; Dan Xu; Shenjie Li; Yueyao Yang; Guohua Zhu; Zhefu Yu; Junpeng Li; Bingcheng Lin; Minghui Zheng; Rong Jin (Journal of Hazardous Materials, 2026)

Patterns of phylogenetic structure across plant life-forms in a large temperate forest and their possible drivers - Yanbo Yang; Danqi She; Yuhong Zhang; Jinghua Yu; Lihua Wang; Huimei Wang; Shijie Han; Wenjie Wang (Biodiversity and Conservation, 2026)

Few-shot natural frequency prediction of Camellia oleifera for vibration harvesting enabled by synthetic data generation - Feng Liu; Dongying Mo; Han Fu; Shaozheng Yu; Xuan Chu; Nan She; Xing Xu; Weizu Wang; Jieli Duan (Computers and Electronics in Agriculture, 2026)

Wenzhouxiangella psychrophila sp. nov., Wenzhouxiangella indolica sp. nov., and Halotectona sediminis gen. nov., sp.nov., three novel taxa with ability of IAA production from saline lake sediment - Qing-Yu Xu; Tayyiba Habib; Lei Gao; Dildar Wu; Xin-Yao Li; Thi-Nhan Khieu; Yue-Heng Chen; Yao Zhang; Yong-Hong Liu; Ting-Ting She; Bao-Zhu Fang; Wen-Jun Li (Systematic and Applied Microbiology, 2026)

Probabilistic reference dose derivation and risk assessment of mycotoxin citrinin for red yeast rice-related foods - Jui-Feng Tsai; She-Yu Chiu; Yu-Syuan Luo; Biing-Hui Liu (Food Research International, 2026)

Egg-free mayonnaise-type emulsions stabilized with whole Spirulina biomass: Rheological, structural, and sensory characterization - Jikang Sui; Yuxuan Cui; Xiangning Lu; Wenhai She; Kangning Wang; Mingkai Bai; Jianwei Yu; Adewale Olusegun Obadina; Guangxin Feng; Haohao Wu (Algal Research, 2026)

Sustainable Spirulina-based nanoemulsions for omega-3 delivery: Exploring the interfacial contributions of proteins and polysaccharides - Jikang Sui; Yuxuan Cui; Xiangning Lu; Wenhai She; Kangning Wang; Mingkai Bai; Jianwei Yu; Guangxin Feng; Haohao Wu; Adewale Olusegun Obadina (Algal Research, 2026)

Laser-based edge-detection system for measuring overland flow depth and instability analysis under laboratory conditions - Ye Tian; Yu Zhu; Dongli She; Yanhe Huang; Fangshi Jiang; Yue Zhang; Jinshi Lin (Computers and Electronics in Agriculture, 2025)

Unraveling river-tide process connectivity in complex deltaic networks - Yajun Wang; Jianliang Lin; Yu Yan; Shuxian Wang; Zhenyan She; Chengyu Jin; Kairong Lin; Tongtiegang Zhao; Giovanni Coco; Huayang Cai (Journal of Hydrology, 2025)

Mechanisms of polyethylene microplastics on microbial community assembly and carbon-nitrogen transformation potentials in soils with different textures - Zijie Yu; Jin Wang; Shu Wang; Yifan Jiang; Jingya Liu; Zhixiang She; Zhengbo Yue (Environmental Research, 2025)

Study on thermal comfort differences between older shoppers and vendors in open-air markets in cold regions - Zhonghai Wang; Lei Li; Mengyao Xiao; Xiaoyi She; Meng Zhen; Yu Shao; Qi Dong; Yansong Li (Energy and Buildings, 2025)

Sustainable production of eicosapentaenoic acid-rich emulsion from Nannochloropsis gaditana by nitrogen regulation and physical cell disruption - Jikang Sui; Ning Zhao; Xiangning Lu; Wenhai She; Kangning Wang; Mingkai Bai; Jianwei Yu; Guangxin Feng; Haohao Wu; Adewale Olusegun Obadina (Bioresource Technology, 2025)

Dose-dependent M2 macrophage polarization induced by Talaromyces marneffei promotes lung cancer cell growth via arginine-ornithine-cycle activation - Anqi Chen; Qian Yu; Leliang Zheng; Junqi Yi; Ziying Tang; Huabo Ge; Yue Ning; Na Yin; Yaohuan Xie; Shengnan Chen; Wenhua Shi; Xiaoling She; et al. (Medical Microbiology and Immunology, 2025)

Platinum-group element geochemistry of the Heigutian FeTi oxide-bearing layered intrusion, Emeishan large igneous province, SW China - Yu-Wei She; Lie-Meng Chen; Song-Yue Yu; Jun-Nian Yi; Hai-Long He (Lithos, 2025)

Origin of rodingites in the Xigaze ophiolite, SW Tibet: Constraints from Ca and Sr isotopes - Yu-Wei She; Jian Sun; Zhi-Yong Zhu; Qiu-Hong Xie; Chen-Xu Pan (Chemical Geology, 2025)

Integrating HS-SPME-GCMS with chemometrics for identifying adulterated flaxseed oils and tracing origins of additives - Yan-Jin Wen; Long-He Wang; Meng Zhai; Hui Ma; Hua-Peng Cui; Lu Han; Guo-Bi Chai; Yi Lv; Qing-Xia Zheng; Yong-Jie Yu; Yuan-bin She (Food Control, 2025)

The threat of microplastics to human kidney health: Mechanisms of nephrotoxicity and future research directions - Ru-Yu Tan; Qin-Ying She; Yun-Ci Ma; Ming-Hong Liu; Li-Juan Li; Li-Li Huang; Yi-Wen Zhong; Hui-Xin Bi (Environmental Research, 2025)

Synergistic microaerobic bio-decontamination of dimethyl sulfide and elemental mercury in the low-O2 content flue gas by a sulfur-oxidizing membrane biofilm reactor - Han-Biao Yang; Lu-Lu Sun; Xiu-Qin Tan; Yuan Zeng; Yu-Qi Huang; Zhen-Shan Huang; She-Jun Chen; Zai-Shan Wei (Chemical Engineering Journal, 2025)

One-step treatment of heavy metal complexes wastewater with phosphorylated zero-valent iron: Regulating 1O2 generation and promoting iron electron release - Liang She; Falong Jia; Zilin Xu; Ying Chen; Jiahui Sun; Zan Luo; Yuanjia Liu; Hao Zhang; Linghao Yu; Zhihui Ai (Chemical Engineering Journal, 2025)

Influence of Long-term Irrigation with Reclaimed Water on the Soil Quality of Different Land Use Types - Zhuo Tian; Dongli She; Hongde Wang; Xiaoqin Sun; Kai Fang; Chao Qiu; Yu Li (Water Resources Management, 2025)

In silico identification for flavor antioxidant compounds in Chrysanthemi flos uncovers the interactions between saccharides and secondary metabolites - Jiamu Ma; Le Wang; Mingxia Li; Jianling Yao; Wei Liu; Feng Zhang; Mengyu Sun; Yu Cao; Yuqing Yang; Yongqi Yang; Letian Ying; Meng Shen; et al. (Food Chemistry, 2025)

Electrospinning preparation of NaA zeolite composite polyacrylonitrile membranes (NaA@PANMs) and studying on adsorption performance for Sr2+ - Yu Liu; Min Yi; Tao Han; Xinlong Li; Linqiao Qin; Yu She; Erna Wei; Kaituo Wang (Environmental Research, 2025)

A specific energy and penetration interaction-based method for optimizing TBM operational parameters in hard rock - Lei She; Cheng-cheng Hu; Yan-long Li; Dong-feng Li; Zhao-Yu Li; Tao Fang; Ji-guang Zheng (Tunnelling and Underground Space Technology, 2025)

Origin of chromitites and dunites of the Dazhuqu ophiolite in the Yarlung-Zangbo ophiolite zone, Tibet - Yu-Wei She; Fa-Hui Xiong; Qiu-Hong Xie (Journal of Asian Earth Sciences, 2025)

Exploring policy support for efficiency improvement of wind power from an environmental perspective: Evidence from wind farms in Qinghai, China - Li-Qiu Liu; Yu-Yan Qin; Xian-Peng Chen; Xiang-Cheng Zhang; Zhen-Yu She; Bai-Chen Xie (Environmental Impact Assessment Review, 2025)

Ultra-stable CO2-aqueous foams for carbon sequestration and internal mineralization in cellular cements - Dingqiang Fan; Xue-Sen Lv; Jian-Xin Lu; Rui Yu; Wei She; Juhyuk Moon; Takafumi Noguchi; Chi Sun Poon (Chemical Engineering Journal, 2025)

Investigating the impact of fecal contamination on antibiotic resistance genes in urban environments using host-associated molecular indicators - Yujing Duan; Hui She; Lingna Jing; Lianrui Duan; Jinxiu Zheng; Ying Shao; Yuxin Che; Yu Shi; Chao Guo; Wenhui Zhao; Tao Yang; Lijun Yang (Environmental Pollution, 2025)

Characteristics of CO2 gasification reaction and biochar structure evolution of rice straw in K2CO3-Na2CO3-Li2CO3 ternary molten salt - Hui She; Peng Lv; Xuanxuan He; Yonghui Bai; Jiaofei Wang; Xudong Song; Weiguang Su; Juntao Wei; Guangsuo Yu (Process Safety and Environmental Protection, 2025)

A brief introduction to PACIAE 4.0 - An-Ke Lei; Zhi-Lei She; Yu-Liang Yan; Dai-Mei Zhou; Liang Zheng; Wen-Chao Zhang; Hua Zheng; Larissa V. Bravina; Evgeny E. Zabrodin; Ben-Hao Sa (Computer Physics Communications, 2025)

Intrinsically-ductile argyrodite solid electrolytes to improve the performance of all-solid-state lithium batteries - Berhanu Degagsa Dandena; Liang-Ting Wu; Tsung-I Yeh; Chia-Yu Chang; Jyh-Chiang Jiang; Dah-Shyang Tsai; Martin Ihrig; Gashahun Gobena Serbessa; Sheng-Chiang Yang; Keseven Lakshmanan; Hwo-Shuenn Sheu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2025)

Efficient and inexpensive preparation of mesoporous silica microspheres and their highly selective adsorption-cycling performance for Ga(III) in acidic solutions - Yu She; Lin Shao; Min Yi; Yong Fang; Linqiao Qin; Yu Liu; Xinpeng Wang; Kaituo Wang (Chemical Engineering Journal, 2025)

Trujillonella humicola sp. nov., a siderophore-synthesizing bacterium isolated from black soil in Northeast China - Ying Wang; Le-Bin Chen; Yu-Ting OuYang; Jia-Ying Xing; Ke Zhang; Nan-Feng Chen; Ting-Ting She; Shuang Wang; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

DHX36-mediated G-quadruplexes unwinding is essential for oocyte and early embryo development in mice - Yu-Xuan Jiao; Guo-Wei Bu; Yun-Wen Wu; Yu-Ke Wu; Bao-Bao Chen; Meng-Ting She; Yi-Hang Zhang; Yu-Jing Lu; Heng-Yu Fan (Science Bulletin, 2025)

Boosting anode interfacial stability in All-Solid-State lithium hybrid batteries with MCMB-Modified stainless steel current collector - Abebe Taye Fenta; Yosef Nikodimos; Semaw Kebede Merso; Ayenew Meniber; Misganaw Adigo Weret; Kassie Nigus Shitaw; Bereket Woldegbreal Taklu; Felika Valencia; Tsung-I Yeh; Chia Lung Hsieh; Chia-Yu Chang; Ya-Jun Liu; et al. (Chemical Engineering Journal, 2025)

Uncertainty analysis of global meteorological drought in CMIP6 projections - Qing Niu; Dunxian She; Jun Xia; Qin Zhang; Yu Zhang; Tianyue Wang (Climatic Change, 2025)

SIDEST: A sample-free framework for crop field boundary delineation by integrating super-resolution image reconstruction and dual edge-corrected Segment Anything model - Haoran Sun; Zhijian Wei; Weiguo Yu; Gaoxiang Yang; Junnan She; Hengbiao Zheng; Chongya Jiang; Xia Yao; Yan Zhu; Weixing Cao; Tao Cheng; Iftikhar Ali (Computers and Electronics in Agriculture, 2025)

Phenolic compounds from Dalbergia odorifera and their hepatoprotective activity - Yu-Jia Zhang; Yan Wen; Kai-Wen Kang; Zhi-Xuan Li; Dong-Li Li; Jing-Wei Jin; Li-She Gan (Phytochemistry Letters, 2025)

Bioassay-guided isolation of terpenoids from Rubus rosifolius - Yihao Yin; Jiehui Li; Qi Cao; Jinxiu Yu; Baoli Chen; Zhigang She; Xiuping Zhang; Bo Wang (Phytochemistry Letters, 2025)

Integrating electrodes and PVDF-HFP/Kevlar nanofiber separator for multi-functions using electrospinning - Zabish Bilew Muche; Yosef Nikodimos; Chia-Yu Chang; Semaw Kebede Merso; Teshager Mekonnen Tekaligne; Kassie Nigus Shitaw; Gashahun Gobena Serbessa; Teklay Mezgebe Hagos; Bereket Woldegbreal Taklu; Tripti Agnihotri; Sheng-Chiang Yang; Jian-Ming Chiu; et al. (Chemical Engineering Journal, 2025)

Rare diphenylheptanoid-phenylheptanoid hybrids with α-glucosidase inhibitory effects from the pollen of Typha angustifolia - Chao Wang; Yu-Peng Li; Xu Gong; Li-She Gan; Hua Zhang (Natural Product Research, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Evaluating the influence of human activities on flood severity and its spatial heterogeneity across the Pearl River Delta - Jing Zhang; Longfei Yu; Jialong Sun; Haibo Liu; Yang Ping; Zhiyong Liu; Yunlong Song; Xiaofeng Hu; Zhenyan She (Science of The Total Environment, 2025)

A carbon footprint assessment for usage of recycled aggregate and supplementary cementitious materials for sustainable concrete: A life-cycle perspective in China - Xiaosong Ma; Haibo Hu; Yu Luo; Wu Yao; Yongqi Wei; Anming She (Journal of Cleaner Production, 2025)

Aquibaculum sediminis sp. nov., a halotolerant bacteria isolated from salt lake sediment - Qing-Yu Xu; Lei Gao; Dildar Wu; Xin-Yao Li; Yong-Hong Liu; Yao Zhang; Yue-Heng Chen; Ting-Ting She; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Effect of calcination temperature on the presence pattern of calcium ions in slag-based geopolymer microspheres and visible light photocatalytic degradation of tetracycline hydrochloride - Linqiao Qin; Lin Shao; Min Yi; Yu She; Yu Liu; Wenwen Chen; Yuxiao Jiang; Kaituo Wang (Journal of Environmental Chemical Engineering, 2024)

Identification and seasonal variation of PM2.5-bound organophosphate flame retardants from industrial parks and the associated human health risk - Helong Ren; Qiang Chen; Zhaofa Huang; Yuhuan Zhu; Jing She; Yingxin Yu (Environmental Pollution, 2024)

Correction: Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Development of fermented Atemoya (Annona cherimola × Annona squamosa)-Amazake increased intestinal next-generation probiotics - Yeu-Ching Shi; She-Ching Wu; Yi-Ching Lin; Yu-Juan Zheng; Cheng-Hao Huang; Bao-Hong Lee (Food Chemistry, 2024)

Modulating stacking mode and molecular polarization in CTF/molecule heterojunction for meliorating photocatalytic CO2 conversion with nearly 100% CO selectivity - Lei Wang; Nan Wang; Jiaxin Mao; Xiaolong Zhao; Yu Xia; Jingwei Huang; Houde She; Xinheng Li; Qizhao Wang (Chemical Engineering Journal, 2024)

Fibrous microplastics in the environment: Sources, occurrence, impacts, and mitigation strategies - Shaochong Liu; Sizhi Liu; Xiangyang Xiao; Lu Liu; Willie Peijnenburg; Yan Xu; Yanhao Wang; Yaqi Yu; Lianzhen Li; Xilin She (Aquatic Toxicology, 2024)

Mechanistic insights into tris(2-chloroisopropyl) phosphate biomineralization coupled with lead (II) biostabilization driven by denitrifying bacteria - Zhen-Shan Huang; Xiu-Qin Tan; Han-Biao Yang; Yuan Zeng; She-Jun Chen; Zai-Shan Wei; Yu-Qi Huang (Science of The Total Environment, 2024)

One-step treatment of Cr(III) complexes wastewater using a P-doped Ti4O7 anode in a compact flow electrolysis device - Liang She; Weixing Zhang; Bo Gao; Hao Zhang; Jundi Cheng; Biao Zhou; Zilin Xu; Jiahui Sun; Ying Chen; Lizhi Zhang; Linghao Yu; Zhihui Ai; et al. (Chemical Engineering Journal, 2024)

Insights into the variations of polycyclic aromatic hydrocarbons and their nitrated and oxygenated derivatives in urban airborne PM2.5 - Yi-Huan Chen; Yuan Zeng; Zhen-Shan Huang; Wen-Qing Mo; Yu-Qi Huang; Tao Wang; She-Jun Chen (Atmospheric Environment, 2024)

Regional Aerosol Optical Depth over Antarctica - Lijing Chen; Minghu Ding; Yong She; Lei Zhang; Zhaoliang Zeng; Jiajia Jia; Yu Zheng; Biao Tian; Kongju Zhu; Xin Wang; Zhendong Yao; Huizheng Che (Atmospheric Research, 2024)

Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Exosomes from Hypoxia-treated Mesenchymal Stem Cells: Promoting Neuroprotection in Ischemic Stroke Through miR-214-3p/PTEN Mechanism - Qian Wu; Jia-Huan Wu; Zhi-Yuan Ye; Wen She; Wen-Jie Peng; Hui-Xin Zhang; Cui Qi; Tian Tian; Xiao-Yu Hou; Jun Gao (Molecular Neurobiology, 2024)

Semi-arid rather than arid regions of China deserve the priority in drought mitigation efforts - Xin Lan; Zhiyong Liu; Yang Ge; Yu Yan; Zhenyan She; Linyin Cheng; Xiaohong Chen (Journal of Hydrology, 2024)

Tree richness increased biomass carbon sequestration and ecosystem stability of temperate forests in China: Interacted factors and implications - Kai Wang; Danqi She; Xiting Zhang; Yuanyuan Wang; Hui Wen; Jinghua Yu; Qinggui Wang; Shijie Han; Wenjie Wang (Journal of Environmental Management, 2024)

Synergetic regulation of interfacial electronic structure of Cu, N co-doped carbon modified TiO2 for efficient photocatalytic CO2 reduction - Houde She; Rui Hua; Jiale Zhao; Yu Xia; Lei Wang; Jingwei Huang; Qizhao Wang (Chemical Engineering Journal, 2024)

Anti-coronavirus and anti-pulmonary inflammation effects of iridoids, the common component from Chinese herbal medicines for the treatment of COVID-19 - Dan-Yu Huang; Yong-Xin Luo; Wen-De Zheng; Shu-Yu Wu; Pei-Qi Huang; Jing-Wei Jin; Pan-Pan Wu; Li-She Gan (Journal of Natural Medicines, 2024)

Enhanced photocatalytic CO2 reduction over Z-scheme β-Ga2O3/TiO2 heterojunction composite catalyst: Synthesis, performance, and mechanism - Rui Hua; Yihang Huang; Yu Xia; Houde She; Lei Wang; Jingwei Huang; Qizhao Wang (Journal of Environmental Chemical Engineering, 2024)

Synergistic effects of modified biochar and selenium on reducing heavy metal uptake and improving pakchoi growth in Cd, Pb, Cu, and Zn–contaminated soil - Xianzhen Li; Yongchao Yu; Yiru Zhang; Jian Wang; Diao She (Journal of Environmental Chemical Engineering, 2024)

Ascorbic acid potentiates photodynamic inactivation mediated by octyl gallate and blue light for rapid eradication of planktonic bacteria and biofilms - Mei-zhi Zheng; Wen-xuan Chen; Yue-xin Zhao; Qiang Fang; Ling-gang Wang; Shi-yi Tian; Yu-gang Shi; Jian-she Chen (Food Chemistry, 2024)

Biodegradable magnesium-based alloy skull repairment (MASR) for skull bone defect: In vitro and in vivo evaluation - Anke Zhang; Xiaoyu Wang; Zeyu Zhang; Xiyue Zhang; Junjie Wang; Yibo Liu; Yan Chen; Jiarui Chen; Ting Chen; Yongjie Wang; Jun Yu; Jia She; et al. (Chemical Engineering Journal, 2024)

Fluoxetine Rescues Excessive Myelin Formation and Psychological Behaviors in a Murine PTSD Model - Chenrui Yin; Kefei Luo; Xinyue Zhu; Ronghang Zheng; Yu Wang; Guangdan Yu; Xiaorui Wang; Fei She; Xiaoying Chen; Tao Li; Jingfei Chen; Baduojie Bian; et al. (Neuroscience Bulletin, 2024)

Comparative pharmacokinetic investigation on crocetin in hyperlipidemia and normal rats after oral administration - Cheng-Ye She; Yuan-Xiong Deng; Qin-Yu Wu; Jing Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Identification and seasonal variation of specific particulate bound (halogenated) polycyclic aromatic hydrocarbons in air from different metal industrial parks in Northwest China - Ziwei Zhang; Qiang Chen; Chifei Bai; Yuhuan Zhu; Jing She; Xiang Ge; Meibao Li; Liangzhong Li; Yingxin Yu (Environmental Science and Pollution Research, 2024)

Titania-immobilized CoOx clusters triggering efficient peroxymonosulfate activation for chloramphenicol degradation - Baoyin Du; Zhilin Ji; Abiduweili Sikandaier; Chenye An; Weidong Zhang; Xinyue Yu; Wenqing Xu; Yukun Zhu; Xilin She (Journal of Environmental Chemical Engineering, 2024)

Inclusion complexes of β-cyclodextrin with isomeric ester aroma compounds: Preparation, characterization, mechanism study, and controlled release - Zuobing Xiao; Peiran Yu; Pingli Sun; Yanxiang Kang; Yunwei Niu; Yuanbin She; Di Zhao (Carbohydrate Polymers, 2024)

Spatiotemporal variations, sources, and atmospheric transformation potential of volatile organic compounds in an industrial zone based on high-resolution measurements in three plants - Jin-Long Mai; Xing-Cong Cai; De-Yao Luo; Yuan Zeng; Yu-Feng Guan; Wei Gao; She-Jun Chen (Science of The Total Environment, 2024)

Climate change dominates the increasing exposure of global population to compound heatwave and humidity extremes in the future - Yiheng Wei; Dunxian She; Jun Xia; Gangsheng Wang; Qin Zhang; Shengzhi Huang; Yu Zhang; Tianyue Wang (Climate Dynamics, 2024)

Risk assessment and strontium isotopic tracing of potentially toxic metals in creek sediments around a uranium mine, China - Pengyuan Deng; Ke Lin; Wenhuan Yuan; Mario Alberto Gomez; Jingye She; Shan Yu; Mengqing Sun; Yanyi Liu; Jin Wang; Diyun Chen; Juan Liu (Chemosphere, 2024)

A novel Fe-loaded porous hydrothermal biochar for removing tetracycline from wastewater: Performance, mechanism, and fixed-bed column - Yu Deng; Jingfan Chen; Ailun She; Fuquan Ni; Wenqing Chen; Tianqi Ao; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Multiple protective layers for suppressing Li dendrite growth and improving the cycle life of anode-free lithium metal batteries - Semaw Kebede Merso; Teshager Mekonnen Tekaligne; Misganaw Adigo Weret; Kassie Nigus Shitaw; Yosef Nikodimos; Sheng-Chiang Yang; Zabish Bilew Muche; Bereket Woldegbreal Taklu; Boas Tua Hotasi; Chia-Yu Chang; Shi-Kai Jiang; Gunther Brunklaus; et al. (Chemical Engineering Journal, 2024)

Anion-trapping composite gel electrolyte for safer and more stable anode-free lithium-metal batteries - Tripti Agnihotri; Shadab Ali Ahmed; Elango Balaji Tamilarasan; Rehbar Hasan; Boas Tua Hotasi; Hailemariam Kassa Bezabh; Steven Suwito; Yosef Nikodimos; Shi-Kai Jiang; Kassie Nigus Shitaw; Zabish Bilew Muche; Pei Yu Huang; et al. (Chemical Engineering Journal, 2024)

Rapid nanomolar detection of Δ9-tetrahydrocannabinol in biofluids via electrochemical aptamer-based biosensor - Yu Xie; Jin-Ping She; Jia-Xing Zheng; Kalle Salminen; Jian-Jun Sun (Analytica Chimica Acta, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Preparation of mixed-mode weak cation exchange magnetic solid-phase extraction sorbent and its application in the extraction of 21 illicit drugs from wastewater - Hongyu Ning; Yilei Fan; Hao Chen; Huijun Liu; Zhongping Huang; Xing Ke; Yu Xu; Yuanbin She (Journal of Hazardous Materials, 2024)

One-step synthesis of iron and nitrogen co-doped porous biochar for efficient removal of tetracycline from water: Adsorption performance and fixed-bed column - Yu Deng; Tong Xiao; Ailun She; Xiaodong Li; Wenqing Chen; Tianqi Ao; Fuquan Ni (Journal of Environmental Management, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Petrogenesis and tectonic implication of the Triassic syenitic complexes in the eastern Qinling orogen, central China - Zhen-Yu Wang; Hong-Rui Fan; Hai-Dong She; Kui-Feng Yang (Journal of Asian Earth Sciences, 2024)

Cultivation and biogeochemical analyses reveal insights into biomineralization caused by piezotolerant iron-reducing bacteria from petroleum reservoirs and their application in MEOR - Hao Dong; Li Yu; Ting Xu; Yulong Liu; Jian Fu; Yanlong He; Ji Gao; Jiaqi Wang; Shanshan Sun; Yuehui She; Fan Zhang (Science of The Total Environment, 2023)

Identification and analysis of alleles in the aroma biosynthesis pathways based on Camellia sinensis ‘Jinguanyin’ haplotype-resolved genomes - Mengya Gu; Ting Gao; Mengting Xu; Yaping Hong; Yibin Wang; Jiaxin Yu; Yuhang Zhang; Wenqin She; Pengjie Wang; Naixing Ye (Trees, 2023)

Unraveling the genomic diversity and ecological potential of the genus Demequina: insights from comparative analysis of different saline niche strains - Lei Gao; Bao-Zhu Fang; Chun-Yan Lu; Kun-Hui Hong; Xin-Yu Huang; Ting-Ting She; Min Xiao; Wen-Jun Li (Frontiers in Marine Science, 2023)
During an investigation of the culturable microbial diversity of sediments with salinity from tidal flats and saline lake, seven strains of the genus Demequina were harvested. The genomic analysis and physiological characteristics of strains of this genus have unveiled their significant potential in degrading complex carbon source such as lignin, hemicellulose, chitin, and oligosaccharides. In addition, these strains show potential abilities in nitrite ammonification and sulfide oxidation. These findings not only improved our understanding of their metabolic model, but also provided valuable insights into their ecological roles. Four new species of the genus Demequina are described: Demequina litoralis sp. nov., with SYSU T00192 T designated as the type species; Demequina zhanjiangensis sp. nov., with SYSU T00b26 T as the type species; Demequina lignilytica sp. nov., with SYSU T00068 T as the type species; and Demequina muriae sp. nov., with EGI L300058 T as the type species. Additionally, strains SYSU T0a273, SYSU T00039-1, and SYSU T00039 are identified as different strains of Demequina lignilytica . Our study thus sheds light on the diversity, biological significance, and ecological contribution of the Demequina genus in different habitats.

Plant selection and ecological microhabitat drive the shrub-associated microbiome selection in revegetated shrub ecosystems - Zongrui Lai; Yanfei Sun; Yang Yu; Zhen Liu; Yuxuan Bai; Yangui Qiao; Lin Miao; Weiwei She; Shugao Qin; Wei Feng (Applied Soil Ecology, 2023)

GlandSegNet: Semantic segmentation model and area detection method for cotton leaf pigment glands - Yaxuan Xu; Guoning Wang; Limin Shao; Nan Wang; Lixuan She; Yu Liu; Yuhong Geng; Geng Yan (Computers and Electronics in Agriculture, 2023)

Disturbance of gut microbiota aggravates cadmium-induced neurotoxicity in zebrafish larvae through V-ATPase - Yongjie Xu; Yongpeng Yu; Qin Zhou; Yang Xiang; Lixuan Chen; Yaxian Meng; Xudong She; Fei Zou; Xiaojing Meng (Science of The Total Environment, 2023)

Isoptericola croceus sp. nov., a novel actinobacterium isolated from saline–alkali soil - Yu-Ting OuYang; Ai-Ping Lv; Lan Liu; Ting-Ting Li; Yi Zhou; Ting-Ting She; Li-Xiang Cao; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Using UHPLC-HRMS-based comprehensive strategy to efficiently and accurately screen and identify illegal additives in health-care foods - Meng-Han Ma; Jia-Ni Zhang; Xing-Ling Ma; Xing-Cai Wang; Feng-Lian Ma; Jia-Nan Liu; Yi Lv; Yong-Jie Yu; Yuanbin She (Food Research International, 2023)

Detecting human interventions by spatial dependence of extreme water levels using a high dimensional conditional probability approach over the Pearl River Delta - Zhenyan She; Liyan Huang; Huayang Cai; Mintao Fan; Longfei Yu; Bo Li; Xin Lan; Xiaohong Chen; Zhiyong Liu (Journal of Hydrology, 2023)

A study of flavor variations during the flaxseed roasting procedure by developed real-time SPME GC–MS coupled with chemometrics - Xing-Ling Ma; Xing-Cai Wang; Jia-Ni Zhang; Jia-Nan Liu; Meng-Han Ma; Feng-Lian Ma; Yi Lv; Yong-Jie Yu; Yuanbin She (Food Chemistry, 2023)

Precisely modulate interfacial Bi-O bridge bond in Co-TCPP/Bi3O4Br to trigger long-lasting charge separation for boosting CO2 photoreduction - Yi Zhang; Fangyu Guo; Keke Wang; Jun Di; Bokki Min; Huiyuan Zhu; Hailong Chen; Yu-Xiang Weng; Jiayu Dai; Yuanbin She; Jiexiang Xia; Huaming Li (Chemical Engineering Journal, 2023)

Isolated and identified pathogenic bacteria from black soldier fly larvae with “soft rot” reared in mass production facilities and its incidence characteristics - Wangjun She; Qi Xiao; Ying Meng; Peng Zhao; Chuanliang Wu; Feng Huang; Minmin Cai; Jibin Zhang; Ziniu Yu; Kashif ur Rehman; Donghai Peng; Longyu Zheng (Waste Management, 2023)

Identification and genomic characterization of Ralstonia pseudosolanacearum strains isolated from pepino melon in China - Shanwen Ding; Lin Yu; Guobing Lan; Yafei Tang; Zhenggang Li; Zifu He; Xiaoman She (Physiological and Molecular Plant Pathology, 2023)

Insight into dissolved organic nitrogen transformation and characteristics: Focus on printing and dyeing wastewater treatment process - Hong Chen; Kai Wang; Shuaiqi She; Xin Yu; Luying Yu; Gang Xue; Xiang Li (Journal of Hazardous Materials, 2023)

A comparison of feature extraction capabilities of advanced UHPLC-HRMS data analysis tools in plant metabolomics - Xing-Cai Wang; Xing-Ling Ma; Jia-Nan Liu; Yang Zhang; Jia-Ni Zhang; Meng-Han Ma; Feng-Lian Ma; Yong-Jie Yu; Yuanbin She (Analytica Chimica Acta, 2023)

Effective adsorption of ammonium nitrogen by sulfonic-humic acid char and assessment of its recovery for application as nitrogen fertilizer - Qianqian Sun; Hanjun Zhou; Chenyang Xu; Yu Ba; Zengchao Geng; Diao She (Science of The Total Environment, 2023)

In-situ solidification of alkali-activated lunar regolith: Insights into the chemical and physical origins - Zifan Geng; Lizhi Zhang; Hao Pan; Wei She; Cheng Zhou; Hao Zhou; Zhenglei Yu; Zhaodong Xu (Journal of Cleaner Production, 2023)

AAZ2 induces mitochondrial-dependent apoptosis by targeting PDK1 in gastric cancer - Yi Li; Wenyan She; Xiaoran Xu; Yixin Liu; Xinyu Wang; Sheng Tian; Shiyi Li; Miao Wang; Chaochao Yu; Pan Liu; Tianhe Huang; Yongchang Wei (Journal of Zhejiang University-SCIENCE B, 2023)

How to solve the dilemma of China’s land fallow policy: Application of voluntary bidding mode in the Yangtze River Delta of China - Zhenning Yu; Shuoqi She; Chuyu Xia; Jiaojiao Luo (Land Use Policy, 2023)

Enhanced removal of typical odor compounds in constructed wetlands integrated with iron carbon and tidal flow - Yuwei She; Yan Zhao; Hongyan Ding; Qian Feng; Zhaoxia Xue; Jingyang Luo; Minfeng Lu; Qian Hu; Jiashun Cao; Yu Dai; Ming Li (Journal of Water Process Engineering, 2023)

Influence of capillary condensation on the adsorption of Br2 in flue gas using a super-fine polyester fiber as adsorbent - Hanxi Xiao; Yong Chi; Yusheng You; Min Ren; Lufen Wu; Hongli Li; Manyuan Li; Xue Shi; Yu She; Dongchan Mao (Journal of Cleaner Production, 2023)

Cooperation of oxygen vacancy and FeIII/FeII sites in H2-reduced Fe-MIL-101 for enhanced Fenton-like degradation of organic pollutants - Chaosheng Bao; Hu Wang; Caiyun Wang; Xiaohui Zhang; Xiaoliang Zhao; Chung-Li Dong; Yu-Cheng Huang; Shuai Chen; Peng Guo; Xilin She; Yuanyuan Sun; Dongjiang Yang (Journal of Hazardous Materials, 2023)

Confined Fe single atomic sites on (100) plane of anatase TiO2 nanofibers boost white LED driven Fenton-like norfloxacin degradation - Zhilin Ji; Rongsheng Cai; Wanneng Ye; Ping Lu; Chung-Li Dong; Yu-Cheng Huang; Xilin She; Denys S. Butenko; Yiming Liu; Yukun Zhu; Dongjiang Yang (Journal of Cleaner Production, 2023)

Genetic variations in the bitter taste receptor gene TAS2R38 are related to cigarette smoking behavior in Han Chinese smokers - Fei-Yan Qi; Zhou-Hai Zhu; Meng Li; Ying Guan; Qi-Yuan Peng; She-Ming Lu; Zhi-Hua Liu; Ming-Feng Wang; Ming-Ming Miao; Zhang-Yu Chen; Xue-Mei Li; Jie Bai; et al. (Genes & Genomics, 2022)

Prediction model for disc cutter wear during hard rock breaking based on plastic removal abrasiveness mechanism - Lei She; She-rong Zhang; Chao Wang; Zheng-qiao Wu; Lun-chuang Yu; Li-xin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Nematicidal activity of volatile organic compounds produced by Bacillus altitudinis AMCC 1040 against Meloidogyne incognita - Lin Ye; Jian-Yu Wang; Xiao-Fang Liu; Qi Guan; Nong-Xiao Dou; Jian Li; Qian Zhang; Yan-Ming Gao; Min Wang; Jian-She Li; Bo Zhou (Archives of Microbiology, 2022)

PM2.5-bound phthalates and phthalate substitutes in a megacity of southern China: spatioseasonal variations, source apportionment, and risk assessment - Yu-Qi Huang; Yuan Zeng; Tao Wang; She-Jun Chen; Yu-Feng Guan; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

Complete genome sequence of a previously undescribed monopartite begomovirus and betasatellite infecting Malvastrum coromandelianum in Cambodia - Yafei Tang; Zhenggang Li; Xiaoman She; Lin Yu; Guobing Lan; Lihua Lv; Judith K. Brown; Zifu He (Archives of Virology, 2021)

CRISPR-Cas adaptive immune systems in Sulfolobales: genetic studies and molecular mechanisms - Zhenxiao Yu; Suping Jiang; Yuan Wang; Xuhui Tian; Pengpeng Zhao; Jianan Xu; Mingxia Feng; Qunxin She (Science China Life Sciences, 2021)

Kinesin-7 CENP-E regulates the formation and structural maintenance of the acrosome - Zhen-Yu She; Kai-Wei Yu; Ya-Lan Wei; Ning Zhong; Yang Lin (Cell and Tissue Research, 2021)

In vitro dual-target activities and in vivo antidiabetic effect of 3-hydroxy-N-(p-hydroxy-phenethyl) phthalimide in high-fat diet and streptozotocin-induced diabetic golden hamsters - Bin Xiao; Yunfeng Xiao; Haining Ning; Xiaoyan Han; Wenyan Li; Yuheng Ma; Na Zhao; Guanhua Du; Yu Dong; Jee H. Jung; Zhanfei She (Medicinal Chemistry Research, 2020)

Seismic spatiotemporal characteristics in the Alpide Himalayan Seismic Belt - Xiaolu Li; Lirong Yin; Li Yao; Wenping Yu; Xiaojun She; Wei Wei (Earth Science Informatics, 2020)

Spatial distribution of the oxygen-18 in precipitation in China based on a new empirical model - Pei Zhao; Zheng-sheng Guo; Dong-li She; Xiang-yu Tang (Journal of Mountain Science, 2019)

Optimization of operating conditions for the acidification metabolites production with waste sludge using response surface methodology (RSM) - Yu Wang; Liang Guo; Jiawen Zhang; Zonglian She; Chunji Jin; Mengchun Gao; Yangguo Zhao (Environmental Science and Pollution Research, 2019)

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

Proteomic discovery of H2O2 response in roots and functional characterization of PutGLP gene from alkaligrass - Juanjuan Yu; Yongxue Zhang; Junming Liu; Lin Wang; Panpan Liu; Zepeng Yin; Siyi Guo; Jun Ma; Zhuang Lu; Tai Wang; Yimin She; Yuchen Miao; et al. (Planta, 2018)

Identification and fine mapping of molecular markers closely linked to fruit spines size ss gene in cucumber (Cucumis sativus L.) - Weiwei Zhang; Yue Chen; Peng Zhou; Wenmin Bao; Xuqin Yang; Taibai Xu; Weiwei She; Liqin Xu; Pinggao Yu; Junsong Pan (Euphytica, 2018)

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Molecular docking, binding free energy analysis, and biological evaluation of bisabolonalone hydrazone carboxamides as H+,K+-ATPase reversible inhibitors - Xin-Xin She; Qing Dong; Hua-Jun Luo; Jun-Zhi Wang; Nian-Yu Huang; Wei-Qiao Deng; Kun Zou (Medicinal Chemistry Research, 2018)

Male-Produced Aggregation Pheromone of Coffee Bean Weevil, Araecerus fasciculatus - Shuai Yang; Xiao-Fang Zhang; Yu-Lin Gao; Dan Chen; Dong-Mei She; Tao Zhang; Jun Ning (Journal of Chemical Ecology, 2017)

Ediacaran macrofossils in Shunyang Valley, Sixi, Three Gorges district, Hubei Province, China - Roger Mason; Yuejie Li; Kenan Cao; Yu Long; Zhen-Bing She (Journal of Earth Science, 2017)

Global ionospheric electron density estimation based on multisource TEC data assimilation - Chengli She; Weixing Wan; Xinan Yue; Bo Xiong; You Yu; Feng Ding; Biqiang Zhao (GPS Solutions, 2017)

Erratum to: Hepatitis E Virus Genotype 4 Sequences Detected in Sewage from Treatment Plants of China - Heng Li; Wei Li; Ruiping She; Liang Yu; Qiaoxing Wu; Jingling Yang; Fengjiao Hu; Majid Hussain Soomro; Ruihan Shi; Wenzhuo Hao; Yue Zhao; Jingjing Mao (Food and Environmental Virology, 2017)

Hepatitis E Virus Genotype 4 Sequences Detected in Sewage from Treatment Plants of China - Heng Li; Wei Li; Ruiping She; Liang Yu; Qiaoxing Wu; Jingling Yang; Fengjiao Hu; Majid Hussain Soomro; Ruihan Shi; Wenzhuo Hao; Yue Zhao; Jingjing Mao (Food and Environmental Virology, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Characterizing scale-specific environmental factors affecting soil organic carbon along two landscape transects - Dongli She; Yutong Cao; Qian Chen; Shuang’en Yu (Environmental Science and Pollution Research, 2016)

The AAA ATPase Vps4 Plays Important Roles in Candida albicans Hyphal Formation and is Inhibited by DBeQ - Yahui Zhang; Wanjie Li; Mi Chu; Hengye Chen; Haoyuan Yu; Chaoguang Fang; Ningze Sun; Qiming Wang; Tian Luo; Kaiju Luo; Xueping She; Mengqian Zhang; et al. (Mycopathologia, 2016)

Nitrogen and phosphorus loss and optimal drainage time of paddy field under controlled drainage condition - Meng-hua Xiao; Shuang-en Yu; Dongli She; Xiu-jun Hu; Lin-lin Chu (Arabian Journal of Geosciences, 2015)

Identification of NS1 domains of avian H5N1 influenza virus which influence the interaction with the NOLC1 protein - Chun-yu Zhu; Fang-liang Zheng; Xiao-shuang She; Dan Zhao; Ying Gu; Yan-ting Duan; Alan K. Chang; Hong-sheng Liu (Virus Genes, 2015)

CTSB promotes porcine preadipocytes differentiation by degrading fibronectin and attenuating the Wnt/β-catenin signaling pathway - Zhen-Yu Zhang; Yin Mai; Hao Yang; Pei-Yue Dong; Xue-Li Zheng; Gong-She Yang (Molecular and Cellular Biochemistry, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

Terfenadine induces anti-proliferative and apoptotic activities in human hormone-refractory prostate cancer through histamine receptor-independent Mcl-1 cleavage and Bak up-regulation - Wei-Ting Wang; Yen-Hui Chen; Jui-Ling Hsu; Wohn-Jenn Leu; Chia-Chun Yu; She-Hung Chan; Yunn-Fang Ho; Lih-Ching Hsu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Rapid dye degradation with reactive oxidants generated by chloride-induced peroxymonosulfate activation - Xiao-Yi Lou; Yao-Guang Guo; Dong-Xue Xiao; Zhao-Hui Wang; Shu-Yu Lu; Jian-She Liu (Environmental Science and Pollution Research, 2013)

Identification and quantitative detection of Legionella spp. in various aquatic environments by real-time PCR assay - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Yi-Chou Chiu; Cheng-Yu She; Shu-Min Shen; Yu-Li Huang; Wen-Chien Huang (Environmental Science and Pollution Research, 2013)

Induction of apoptosis through caspase-independent or caspase-9-dependent pathway in mouse and human osteosarcoma cells by a new nitroxyl spin-labeled derivative of podophyllotoxin - Tuan-Min Yang; She-Ning Qi; Na Zhao; Yu-Jie Yang; Hu-Qin Yuan; Bing Zhang; Shuai Jin (Apoptosis, 2013)

Transpiration and canopy conductance of Caragana korshinskii trees in response to soil moisture in sand land of China - Dongli She; Yongqiu Xia; Mingan Shao; Shizhang Peng; Shuangen Yu (Agroforestry Systems, 2013)

Endothelin-1 Stimulates the Expression of L-Type Ca2+ Channels in Neonatal Rat Cardiomyocytes via the Extracellular Signal–Regulated Kinase 1/2 Pathway - Liangzhu Yu; Mincai Li; Tonghui She; Chunrong Shi; Wei Meng; Banghua Wang; Menglin Cheng (The Journal of Membrane Biology, 2013)

The SOX gene family: function and regulation in testis determination and male fertility maintenance - Ting Jiang; Cong-Cong Hou; Zhen-Yu She; Wan-Xi Yang (Molecular Biology Reports, 2013)

The impact of catastrophic natural disaster on land-use changes of Qingping town and the selection of suitable land for settlement construction - Hui Yu; Shaoquan Liu; Shili Guo; Ying Hu; Zhijun Zheng; Tao She (Journal of Mountain Science, 2012)

Regression analysis between environmental factors and earthquake-damaged trace: a case study in Wenchuan County, China - Yong Luo; Hui Yu; Zhi-Jun Zheng; Tao She (International Journal of Remote Sensing, 2012)

The influence of water content on soil erosion in the desertification area of Guizhou, China - Jie Zhou; Yi-qun Tang; Xiao-hui Zhang; Tian-yu She; Ping Yang; Jian-xiu Wang (Carbonates and Evaporites, 2012)

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Screening Level of PAHs in Sediment Core from Lake Hongfeng, Southwest China - Jian-Yang Guo; Feng-Chang Wu; Liang Zhang; Hai-Qing Liao; Run-Yu Zhang; Wei Li; Xiao-Li Zhao; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2011)

Methotrexate ameliorates pristane-induced arthritis by decreasing IFN-γ and IL-17A expressions - Wei-kun Hou; Lie-su Meng; Fang Zheng; Yu-rong Wen; Wen-hua Zhu; Cong-shan Jiang; Xiao-jing He; Yan Zhou; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2011)

Polybrominated Diphenyl Ethers (PBDEs), Polychlorinated Biphenyles (PCBs), Hydroxylated and Methoxylated-PBDEs, and Methylsulfonyl-PCBs in Bird Serum from South China - Juan Liu; Xiao-Jun Luo; Le-Huan Yu; Ming-Jing He; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2010)

N2O fluxes from the native and grazed semi-arid steppes and their driving factors in Inner Mongolia, China - Xing-Ren Liu; Yun-She Dong; Yu-Chun Qi; Sheng-Gong Li (Nutrient Cycling in Agroecosystems, 2010)

Regulation of ATGL expression mediated by leptin in vitro in porcine adipocyte lipolysis - Yu-cheng Li; Xue-li Zheng; Bing-ting Liu; Gong-she Yang (Molecular and Cellular Biochemistry, 2010)

Tissue expression of porcine FoxO1 and its negative regulation during primary preadipocyte differentiation - Wei-Jun Pang; Tai-Yong Yu; Liang Bai; Yan-Jun Yang; Gong-She Yang (Molecular Biology Reports, 2009)

Assessment of sampling designs to measure riverine fluxes from the Pearl River Delta, China to the South China Sea - Hong-Gang Ni; Feng-Hui Lu; Xian-Lin Luo; Hui-Yu Tian; Ji-Zhong Wang; Yu-Feng Guan; She-Jun Chen; Xiao-Jun Luo; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Alteration of mitochondrial oxidative capacity during porcine preadipocyte differentiation and in response to leptin - Gui-Fen Luo; Tai-Yong Yu; Xu-Hui Wen; Ying Li; Gong-She Yang (Molecular and Cellular Biochemistry, 2007)

Factors Contributing to Troponin Exchange in Myofibrils and in Solution - Mingda She; David Trimble; Leepo C. Yu; Joseph M. Chalovich (Journal of Muscle Research and Cell Motility, 2000)